KARAKTERISTIK MINYAK ATSIRI DAUN MUDA MEDANG PIRAWAS (Litsea Elliptica Blume) DENGAN METODE DISTILASI UAP - Indri Astuti Handayani; Supomo; Ika Agustina; Agus Wira; Nurlaili Ruwaida N (Jurnal Farmasi IKIFA, 2023)
Indonesia has enormous biodiversity. This is proven by the fact that 40 species of the world's 99 essential oil-producing plants are found in Indonesia. On the island of Kalimantan there are plants that have the potential to produce essential oils such as Litsea elliptica Blume. Essential oil from Litsea elliptica Blume leaves has no toxic effects when used according to WHO guidelines. Apart from that, Litsea elliptica Blume also has antioxidant and antimicrobial effects. This research aims to determine the composition contained in the essential oil of young leaves of Litsea elliptica Blume. Refining essential oils uses the steam distillation method. Then, proceed with analyzing the composition of chemical compounds in Litsea elliptica Blume essential oil using the Gas Chromatography-Mass Spectrometry (GC-MS) method. The essential oil of young leaves of Litsea elliptica Blume contains 42 chemical compounds with 2-Undecanone as the largest composition, namely 14.5322%. The composition of chemical compounds that have benefits as fragrances include Cyclohexanemethanol.alpha.,.alpha.,4-trimethyl-, 2-Nonanone, 2-Undecanol, 2-Undecanone, 6,10-dimethyl-, Patchouli alcohol.